Young, American Indian or Alaskan Native, and born in the USA: at excess risk of starting extra-medical prescription pain reliever use? - Parker,Maria A.; Lopez-Quintero,Catalina; Anthony,James C. (PeerJ, 2018)
Background Prescription pain reliever (PPR) overdoses differentially affect ‘American Indian/Alaskan Natives’ in the United States (US). Here, studying onset of extra-medical PPR use in 12-24-year-olds, we examine subgroup variations in rates of starting to use prescription pain relievers extra-medically (i.e., to get ‘high’ or for other reasons outside boundaries of prescriber’s intent). Risk differences (RD) are estimated for US-born versus non-US-born young people, stratified by American Indian/Alaskan Natives versus other ethnic self-identities. Methods Between 2002–2009, nationally representative cross-sectional samples of 12–24-year-old non-institutionalized civilians completed interviews for the US National Surveys of Drug Use and Health. Analysis-weighted annual incidence estimates, RD, and confidence intervals (CI) are from the Restricted-use Data Analysis System, an online software tool for US National Surveys of Drug Use and Health. Results Each year, an estimated 2.5% of 12-24-year-olds in the US start using PPR extra-medically (95% CI [2.1%–3.0%]). Estimates for the US-born (3.8%; 95% CI [3.7%–3.9%]) are larger (non-US-born: 1.8%; 95% CI [1.5%–2.0%]; RD = 2.0; p < 0.05). US-born American Indian/Alaskan Natives youths have the largest incidence rate (4.8%). Robust RD for US-born can be seen for ‘non-Hispanic White’ subgroups, and for others (e.g., ‘Cuban’, ‘Dominican’). Discussion Each year, one in 20 of US-born American Indian/Alaskan Natives starts using PPR extra-medically. Overdose prevention is important, but is no substitute for primary prevention initiatives for all young people. The observed epidemiological patterns can guide targeted prevention initiatives for the identified higher risk subgroups in complement with more universal prevention efforts intended to reduce incidence of first extra-medical PPR use, a crucial rate-limiting step on the path toward more serious drug involvement (i.e., progressing past initial use).
Keywords: Opioids; Adolescents; Foreign-born; US-born; Prescription pain relievers